Lithospheric architecture of the South-Western Alps revealed by multiparameter teleseismic full-waveform inversion. Issue 2 (3rd November 2017) - Beller, S; Monteiller, V; Operto, S; Nolet, G; Paul, A; Zhao, L
Summary: The Western Alps, although being intensively investigated, remains elusive when it comes to determining its lithospheric structure. New inferences on the latter are important for the understanding of processes and mechanisms of orogeny needed to unravel the dynamic evolution of the Alps. This situation led to the deployment of the CIFALPS temporary experiment, conducted to address the lack of seismological data amenable to high-resolution seismic imaging of the crust and the upper mantle. We perform a 3-D isotropic full-waveform inversion (FWI) of nine teleseismic events recorded by the CIFALPS experiment to infer 3-D models of both density and P - and S -wave velocities of the Alpine lithosphere. Here, by FWI is meant the inversion of the full seismograms including phase and amplitude effects within a time window following the first arrival up to a frequency of 0.2 Hz. We show that the application of the FWI at the lithospheric scale is able to generate images of the lithosphere with unprecedented resolution and can furnish a reliable density model of the upper lithosphere. In the shallowest part of the crust, we retrieve the shape of the fast/dense Ivrea body anomaly and detect the low velocities of the Po and SE France sedimentary basins. The geometry of the Ivrea body as revealed by our density model is consistent with the Bouguer anomaly. A sharp Moho transition is followed from the external part (30 km depth) to the internal part of the Alps (70–80 km depth), giving clear evidence of a continental subduction event during the formation of the Alpine Belt. A low-velocity zone in the lower lithosphere of the S -wave velocity model supports the hypothesis of a slab detachment in the western part of the Alps that is followed by asthenospheric upwelling. The application of FWI to teleseismic data helps to fill the gap of resolution between traditional imaging techniques, and enables integrated interpretations of both upper and lower lithospheric structures.